Peri-prosthetic humeral non-union: Where biology meets bio-mechanic. A case report - Emanuele, Ciurlia (Int J Surg Case Rep, 2017)
INTRODUCTION: The worldwide incidence of traumatic fractures has been growing over the last years due to the progressive aging of the population. Today, the increase of arthroplasty procedures in orthopaedic surgery is related to a high rate of peri-prosthetic fractures. Healing of the fracture is a multifactorial metabolic process; if these factors are impaired, healing process could be interrupted resulting in non-union. PRESENTATION OF CASE: We report our experience about a case of a humeral diaphysis non-union secondary to peri-prosthetic fracture (reverse shoulder arthroplasty) treated by conservative approach. DISCUSSION: We treated this patient using a multilevel approach, consisting of revision surgery and drug therapy. CONCLUSION: We assume that an aggressive revision surgery done with bone autograft implant and a bone healing therapy administering teriparatide off-label can reduce the convalescence in non-unions and can improve prognosis.